2010
DOI: 10.1002/jmor.10876
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy and osteohistology of hyperelongate neural spines in the sphenacodontids Sphenacodon and Dimetrodon (Amniota: Synapsida)

Abstract: Osteohistological investigations of hyperelongate vertebral spinous processes (neural spines) are presented to elucidate previously unknown aspects of dorsal sail form and function in two, closely related genera of "sail-backed" synapsids: Sphenacodon and Dimetrodon. Although recent and classic surveys of bone histology in extinct vertebrates have sampled the genus Dimetrodon, new sectioning of Sphenacodon material allows a comparative analysis of these structures among Sphenacodontidae for the first time. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…(Huttenlocker and Rega, 2012) and Dimetrodon natalis (Shelton et al, 2013; see also Huttenlocker et al, 2010).…”
Section: Comparative Data On Bone Histologymentioning
confidence: 99%
“…(Huttenlocker and Rega, 2012) and Dimetrodon natalis (Shelton et al, 2013; see also Huttenlocker et al, 2010).…”
Section: Comparative Data On Bone Histologymentioning
confidence: 99%
“…Sphenacomorpha is the only group of medium-to-large bodied non-mammalian synapsids to have developed elongate neural spines forming a dorsal sail, the function of which has been subject to intense scrutiny (Romer 1927;Rodbard 1949;Pivorunas 1970;Bramwell and Felqett 1973;Haack 1986;Tracy et al 1986;Bennett 1996;Florides et al 2001;Huttenlocker et al 2010Huttenlocker et al , 2011Tomkins et al 2010;Rega et al 2012). It has been suggested that sphenacomorphs were the largest terrestrial vertebrates of the Permo-Carboniferous because of their dorsal sails, as the sail would act to strengthen the vertebral column at large body masses and increase the efficiency of thermoregulation (Romer 1927;Pivorunas 1970;Florides et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that sphenacomorphs were the largest terrestrial vertebrates of the Permo-Carboniferous because of their dorsal sails, as the sail would act to strengthen the vertebral column at large body masses and increase the efficiency of thermoregulation (Romer 1927;Pivorunas 1970;Florides et al 2001). Recent studies have questioned the use of the dorsal sail as a thermoregulatory organ based on histological analyses of the neural spines (Huttenlocker et al 2010(Huttenlocker et al , 2011, the suggestion that Dimetrodon was nocturnal (Angielczyk and Schmitz 2014), and the positive allometry of neural spine height through evolutionary time as evidence that the sail was used for sexual selection (Bakker 1986;Tomkins et al 2010). However, the idea of whether or not dorsal sails are related to body size in sphenacomorphs has never been quantitatively tested.…”
Section: Introductionmentioning
confidence: 99%
“…These include the possible occurrence of cysts in Brazilian rhynchosaurs (Schultz 1999), avascular necrosis in mosasaurs (Rothschild and Martin 1987), osteoarthritis in plesiosaurs (Wells 1964), osteomyelitis in crocodilians (Ferigolo 1993a), bone infections in aetosaurs (Lucas 2000), fractures and infections in dinosaurs (Rothschild 1988;Hanna 2002;Peterson et al 2009), and luxations, exostoses and arthrosis in mammals (Moodie 1930;Choquette et al 1975;Ferigolo 1985Ferigolo , 1993bLucas and Schoch 1987;Wang and Rothschild 1992;Gillette and Madsen 1993;Henriques et al 1998;Scott and Rooney 2001). Recently, there has been increasing interest in pathological features of basal synapsids (Huttenlocker et al 2010;Huttenlocker and Rega 2012) and other Paleozoic tetrapods (Reisz et al 2011). Among dicynodonts, pathologies have been reported on several occasions.…”
Section: Introductionmentioning
confidence: 99%